1984
DOI: 10.1161/01.hyp.6.5.736
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships between blood pressure, sodium, potassium, serum cholesterol, and protein intake in Japanese.

Abstract: MASAHIRO KIHARA, JUN FUJIKAWA, MICHIYA OHTAKA, MASAYUKI MANO, YASUO NARA, RYOICHI HORIE, TOKUGORO TSUNEMATSU, SHINYA NOTE, MASAICHI FUKASE, AND YUKIO YAMORI SUMMARY Interrelationships among blood pressure (BP), sodium (Na), potassium (K), dietary protein, and serum cholesterol level (Choi) were examined in 62% (1120) of 1818 Japanese inhabitants of both sexes aged over 30 years who lived in a rural village in Japan. Fasting single-spot urine specimens were collected in the morning to measure Na, K, urea nitrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1
1

Year Published

1988
1988
2004
2004

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 26 publications
2
36
1
1
Order By: Relevance
“…[40][41][42] These concordant results led to renewed attention to earlier Japanese findings, indicating an independent inverse relation of dietary protein to BP. [26][27][28][29] Chinese epidemiologic studies also indicated such an influence on BP of dietary protein, and of individual amino acids. [43][44][45] In the late 1980s and early 1990s, reports were published on randomized trials on amount and type of protein, especially vegetable vs animal protein, and BP.…”
Section: Other Studies On Diet and Blood Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…[40][41][42] These concordant results led to renewed attention to earlier Japanese findings, indicating an independent inverse relation of dietary protein to BP. [26][27][28][29] Chinese epidemiologic studies also indicated such an influence on BP of dietary protein, and of individual amino acids. [43][44][45] In the late 1980s and early 1990s, reports were published on randomized trials on amount and type of protein, especially vegetable vs animal protein, and BP.…”
Section: Other Studies On Diet and Blood Pressurementioning
confidence: 99%
“…[22][23][24] It was also reported that vegetarian peoples had lower SBP/DBP than omnivorous 'Westerners', but these papers lacked data on specific ingested nutrients. 25 In the late 1970s and early 1980s, Japanese researchers published data from population studies and animal experiments suggesting an inverse relation of dietary protein (particularly animal protein) to BP [26][27][28][29] Fin contrast to judgements of 'Western' researchers who hypothesized a direct association of protein with BP, or concluded in reviews that the limited available data indicated no relationship. 30,31 INTERSALT Neglect of the nutrition-BP issue began to change in the latter 1980s, in part as a result of the INTERSALT Study.…”
mentioning
confidence: 99%
“…Nonetheless, the weak relationship is of interest, as it is consistent with earlier findings in adult blacks. [24][25][26][27][28][29] McGarvey et al 30 found that maternal K intake during pregnancy correlated inversely with diastolic BP measured when their babies had reached the age of 6 and 12 months. A number of studies have reported an inverse relationship between BP and K intake during infancy and childhood.…”
Section: Potassium Intake and Blood Pressurementioning
confidence: 99%
“…This dietary protein-BP association was stronger in men than in women, but the coefficients in both genders appeared to be fairly small (ranging from 0.014 to 0.03). This small association may be explained in part by the potential competition risks of multi-factorial effect on BP, such as the associations of BP with salt intake, body mass index, potassium, calcium etc., which have been confirmed to have strong effect on BP in several studies (7,10,13,(26)(27)(28). However, if we consider the long-term effect of such an association and its inter-relation with other factors, a small but significant protein-BP association might play an important role in regulating BP.…”
Section: Discussionmentioning
confidence: 78%
“…Eleven cross-sectional studies (6,7,(12)(13)(14)(15)(16)(17)(18)(19)(20) were examined (Table 1), and nine of them were found to be suitable for the present meta-analyses (6,7,12,(14)(15)(16)(18)(19)(20). Table 2 shows the regression coefficients of BP on dietary protein intake for each study; in case in which these coefficients were not reported, they were estimated using the relevant data (see Methods).…”
Section: Cross-sectional Studiesmentioning
confidence: 99%